E-Service Quality And Trust Within B2C E-Commerce Environment: A Study On Internet Banking In Malaysia - Stephanus, Richard (2006)
This thesis is produced to provide fundamental platform to meet the future of Internet banking expectation in term of E-service quality expectation and to enhance trust conception.